Discrimination Based on Sexual Orientation “Homophobia in Healthcare Employees”: a Cross-Sectional Study - Değer, Vasfiye Bayram; Kaçan, Havva (Springer Science and Business Media LLC, 2024)
Abstract Introduction The study was conducted to examine the attitudes of healthcare employees toward homosexuals and the factors affecting them, while homophobic thoughts and behaviors are based on heteronormative cultural beliefs and gender stereotypes. Methods This study was planned as a cross-sectional and completed with 720 healthcare employees. The Demographic Information Form and Hudson and Ricketts Homophobia Scale were used in the study. Data were collected between January 06 and January 10, 2022. Results The mean homophobia total score of the employees was determined as 97,503 ± 25,807. Homophobia levels of male healthcare employees, those who thought homosexuality is a disease, and those who stated that homosexuality can be caused by taking an example had increasing homophobia levels. The level of homophobia decreases in the presence of homosexual friends, those who can talk freely about homosexuality, and healthcare employees who support same-sex marriage. Conclusions Recognition of individuals with different sexual orientations by healthcare employees will reduce homophobic attitudes toward these individuals. Examining the level of homophobia in healthcare institutions and ensuring that discriminatory attitudes or behaviors toward individuals from different sexual orientations are determined to be effective on the quality of healthcare and access to healthcare services. Policy Implications There is a healthcare system in which patients are generally assumed to be heterosexual; healthcare employees are not prepared to work with Lesbian, Gay, Bisexual, and Transsexual patients in general. Studies conducted on this subject indicate that more studies are needed on the subject to implement a healthcare policy focusing on sexual diversity in healthcare services and to discuss healthcare practices for the Lesbian, Gay, Bisexual, and Transsexual population.
Keywords: Hospital; Turkey; Gender; Homophobia; Mardin; Health care employees; LGBTIQ +; 10. No inequality; 3. Good health